Autonomous Non‐Equilibrium Self‐Assembly and Molecular Movements Powered by Electrical Energy. (22nd December 2022) - Ragazzon, Giulio; Malferrari, Marco; Arduini, Arturo; Secchi, Andrea; Rapino, Stefania; Silvi, Serena; Credi, Alberto
Abstract: The ability to exploit energy autonomously is one of the hallmarks of life. Mastering such processes in artificial nanosystems can open technological opportunities. In the last decades, light‐ and chemically driven autonomous systems have been developed in relation to conformational motion and self‐assembly, mostly in relation to molecular motors. In contrast, despite electrical energy being an attractive energy source to power nanosystems, its autonomous harnessing has received little attention. Herein we consider an operation mode that allows the autonomous exploitation of electrical energy by a self‐assembling system. Threading and dethreading motions of a pseudorotaxane take place autonomously in solution, powered by the current flowing between the electrodes of a scanning electrochemical microscope. The underlying autonomous energy ratchet mechanism drives the self‐assembly steps away from equilibrium with a higher energy efficiency compared to other autonomous systems. The strategy is general and might be extended to other redox‐driven systems. Abstract : By controlling the potential of two electrodes simultaneously, a strategy has been implemented that uses electrical energy to drive self‐assembling systems away from equilibrium. The proposed approach has been demonstrated by modulating the self‐assembly of a calix[6]arene host with a viologen guest, using a scanning electrochemical microscope setup. High thermodynamic efficiencies are obtained.